Solution Of Convective Boundary Layer Flows Via Scaling Group Transformation Method - Mutlag Al-Assafi, Ali Abid (2014)

(untitled)
The aim of this thesis is to find similarity solutions for some models in fluid mechanics using the method of scaling group transformation. In this thesis the steady two-dimensional incompressible laminar boundary layer on a flat plate as well as wedge flow models both in porous media and clear media have been studied. Tujuan tesis ini adalah untuk mencari penyelesaian keserupaan bagi beberapa model dalam mekanik bendalir menggunakan kaedah penjelmaan kumpulan penskalaan. Dalam tesis ini aliran lapisan sempadan berlamina dua dimensi tak boleh mampat yang mantap pada plat rata dan baji di dalam media berliang dan tidak berliang telah dikaji.